The Youth tourist : motives, experiences and travel behaviour - Irimiás, Anna (Emerald Publishing Limited, 2023)
Youth tourists are often defined as money poor and time rich but there are significant differences in social status, interests, and consumption behaviour within the various segments of this sector. In The Youth Tourist: Motives, Experiences and Travel Behaviour, author Anna Irimiás maps out the heterogenous segment of the 'Millennial' market to help illustrate the rich diversity of youth tourist motivations and behaviours. Drawing on theories found in social psychology, media, and communication and consumer behaviour to describe youth tourists on family holidays, on study and working abroad programs, and participating in pilgrimages, festivals, and media-induced tourism events, Irimiás adds significant detail to youth tourist travel patterns in light of current societal changes. She also analyses future trends in youth tourism and addresses the implications of current challenges such as climate change and digitalization, and the potential changes to the industry in light of the pandemic. The Youth Tourist presents new perspectives to researchers of Tourism Studies and the Sociology of Travel who are looking for a contemporary and critical analysis of this important market sector.
Keywords: Youth -- Travel.; Tourism.; Travel, Special Interest -- General.; Tourism industry.; elektronické knihy; electronic books